Sweet talk: communication practices and perceptions at an urban clinic for Gestational Diabetes Mellitus - Burkett, Bianca (My University, 2015)
Background: Gestational Diabetes Mellitus (GDM) is a complex condition that is prevalent in South Africa. South Africa poses a uniquely diverse population and this diversity has the potential to compound communicative interactions, particularly within the healthcare context. Previous research has identified links between communication practices and patients’ health outcomes and attitudes towards conditions and treatment. However, these links have not been explored in the field of GDM in South Africa. Furthermore, little attention has been given to issues related to patients’ lifeworlds, empowerment, nursing, stigma and information-giving in the context of GDM in South Africa. Aim: This study aims to explore the communication practices and perceptions of nurses and patients at an urban GDM clinic in South Africa. Methods: Qualitative methods of inquiry were used, including ethnographic observations, focus groups (4 groups with a total of 19 patients), semi-structured interviews (12 interviews) and video recordings of nurse-patient interactions (6 recorded interactions). Purposive sampling was adopted. Data analysis included thematic analysis and an interactional analysis of the nurse-patient interactions at the clinic. Findings: Multiple themes, facilitators and barriers to communication emerged, including communication difficulties between nurses and patients, patient dissatisfaction with communication at the clinic, uncertainty about GDM and living with the condition, negative attitudes and preconceptions among nurses, intraprofessional conflict and environmental barriers. Findings suggested limited communication at the clinic, due to inadequate information giving, cultural and linguistic mismatch, a lack of skills and knowledge amongst nurses, resource shortages, differing nurse-patient agendas and negative attitudes of nurses and patients. A paradox between patient reports and observations at the clinic also emerged. All of these factors appeared to affect the satisfaction, lifeworld, empowerment and attitudes of the patients attending the clinic, as well as nurses’ job satisfaction. These findings highlighted important implications related to staff training, collaboration and practice at the site, future research into communication practices at the clinic and the effect of possible interventions and research into living with GDM in South Africa. Implications for policy relating to GDM and communication practices will be discussed. Conclusion: This study highlights the importance of communication in facilitating positive health outcomes, attitudes, satisfaction and treatment adherence, especially in such a diverse population. The findings inform important implications related to communication training at the GDM clinic and other similar contexts in South Africa, as well as other pertinent recommendations.
A report on a study project presented to The Discipline of Speech Pathology School of Human and Community Development Faculty of Humanities University of the Witwatersrand In fulfilment of the requirements For the degree M.A. Speech Pathology 1 June, 2015